Selective photostimulation of genetically chARGed neurons. - Zemelman, B; Lee, G; Ng, M; Miesenböck, G (2002)
To permit direct functional analyses of neural circuits, we have developed a method for stimulating groups of genetically designated neurons optically. Coexpression of the Drosophila photoreceptor genes encoding arrestin-2, rhodopsin (formed by liganding opsin with retinal), and the alpha subunit of the cognate heterotrimeric G protein--an explosive combination we term "chARGe"--sensitizes generalist vertebrate neurons to light. Illumination of a mixed population of neurons elicits action potentials selectively and cell-autonomously in its genetically chARGed members. In contrast to bath-applied photostimulants or caged neurotransmitters, which act indiscriminately throughout the illuminated volume, chARGe localizes the responsiveness to light. Distributed activity may thus be fed directly into a circumscribed population of neurons in intact tissue, irrespective of the spatial arrangement of its elements.